ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI - Catur Nur Afni; Meliza Meliza; Anggrainy Putri Ayuningrum (Jurnal Ekonomi dan Bisnis, 2023)
The company value perceived by investors towards the company is often associated with the stock price. The higher of  company’s value can increase investor and make good profitability. This study aims to analyze the effect of profitability, firm size, and liquidity on firm value with capital structure as a moderating variable. The population in this study are food and beverage companies listed on the indonesia stock exchange (idx) for 2019-2021. The sample in this company is 84 companies, the sampling method uses purposive sampling. The type of data used is classic asumtion, multiple linear regression, and moderated regression analysis (mra). Hypothesis test using model fitment test and partial test or t test. The results of this study show that partially the variable return on assets has a significant positive effect on price to book value, firm size has an insignificant positive effect on price to book value, and current ratio has a negative but insignificant effect on price to book value. Capital structure cannot moderate the relationship between profitability and price to book value, capital structure cannot moderate the relationship between firm size and price to book value, and capital structure cannot moderate the relationship between current ratio and price to book value.